Evolution and procedures in central banking - Altig, David 1956-; Smith, Bruce D. -2002 (Cambridge University Press, 2003)
This volume collects the proceedings from a conference on the evolution and practice of central banking sponsored by the Central Bank Institute of the Federal Reserve Bank of Cleveland. The articles and discussants' comments in this volume largely focus on two questions: the need for central banks, and how to maintain price stability once they are established. The questions addressed include whether large banks (or coalitions of small banks) can substitute for government regulation and due central bank liquidity provision; whether the future will have fewer central banks or more; the possibility of private means to deliver a uniform currency; if competition across sovereign currencies can ensure global price stability; the role of learning (and unlearning) the lessons of the past inflationary episodes in understanding central bank behavior; and an analysis of the European Central Bank
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Banks and banking, Central; Stabilitätspolitik; Notenbankpolitik; Geldpolitik; Währungsunion; Notenbank; Inflationsbekämpfung; Konferenzschrift -- 2001 -- Cleveland Ohio